2015
DOI: 10.1007/s00134-015-3718-0
|View full text |Cite
|
Sign up to set email alerts
|

Do we need a pharmacist in the ICU?

Abstract: On the surface, the answer to the question of the title of this editorial seemed to be a rhetorical and obvious yes. This is not because two pharmacists are involved in authoring this editorial, but because there is a substantial amount of literature-arguably more than which exists for any other clinical team member in the ICU and likely more than some of the standard-of-care interventions (such as mechanical ventilation)-which linked the presence of a pharmacist in an ICU to improved patient outcomes.Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Clinical pharmacists make an essential contribution to the safe and effective use of medicines in critically ill patients 1. Direct patient care via pharmacist medication review is an important resource for reducing medication errors and optimising medication use 2.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pharmacists make an essential contribution to the safe and effective use of medicines in critically ill patients 1. Direct patient care via pharmacist medication review is an important resource for reducing medication errors and optimising medication use 2.…”
Section: Introductionmentioning
confidence: 99%
“…The e‐Delphi consensus process identified the perceived value by a UK critical care pharmacist group of some interventions/ resources commonly employed by critical care units. Healthcare staff are an effective barrier to medication errors in critical care units . The process recognised the importance of not only provision of clinical pharmacist activity, but also the need for specialist advanced‐level of pharmacists .…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare staff are an effective barrier to medication errors in critical care units . The process recognised the importance of not only provision of clinical pharmacist activity, but also the need for specialist advanced‐level of pharmacists . The latter may reflect the combined direct clinical activity and professional support roles (clinical guidelines, education and participation in clinical incident review and response)…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been published from resource-limited settings evaluating patient outcomes related to nurse-to-patient ratios. Evidence from resource-limited settings confirms the benefits of including pharmacists into the multidisciplinary ICU team on patient outcomes [17]. Studies from China, Thailand, Jordan, Egypt, and Vietnam demonstrated consistent reductions in medication costs [33][34][35] and adverse events [36] after involvement of a pharmacist in daily ICU practice.…”
Section: Staffingmentioning
confidence: 92%
“…Notably, a higher nurse-to-patient ratio prevents burnout of nurses [16]. Studies in resource-rich settings also suggest that the presence of allied healthcare professionals like pharmacists [17], respiratory or physical therapists [18], and dieticians [19] within a multidisciplinary ICU team improves patient outcomes [3]. Furthermore, proactive communications with infectious disease specialists or microbiologists favorably affect antibiotic use and costs [20].…”
Section: Staffingmentioning
confidence: 99%